FR1.2: Understanding Community Perceptions of Women Empowerment for Agricultural and Rural development - Nakyewa, Brenda; Mangheni, Margaret Najjingo; Businge Martha; Angudubo, S.; Shimali, Fred; Nanyonjo, G.; Asiimwe, E.; Sanya, Losira N. (Makerere University, 2022)
The concept of women empowerment has been widely embraced in development efforts aimed at achieving gender equality outcomes. However, intended outcomes are not always achieved due to a disconnect between how the concept of women empowerment is perceived by target communities and development actors. An understanding of how targeted communities perceive women empowerment helps development actors design context specific women empowerment approaches suited to prevailing social cultural norms and perceptions of men and women. This study therefore aims at understanding perceptions of women empowerment by local communities in rural farming villages of Kiboga district in central Uganda. A qualitative case study design was used to collect data on community perceptions about women empowerment through key informants and sex-disaggregated focus group discussions. The data were coded using Atlas Ti and analyzed to identify themes. We found that men perceived an empowered woman as un-submissive, and a competitor to men's household head position. To women, an empowered woman was perceived as un-submissive, hardworking and taking over culturally assigned men's household responsibilities. As women get empowered, what do men become and at what cost to women? Findings indicate that an empowered woman takes over the responsibilities of an "ideal man" and this adds work burden to women and a backlash from men. In order to counter this, development agencies should target men and women and invest in interventions and approaches that transform local gender norms that dis-empower women. The study is ongoing and further data collection will be completed in August 2022.